Identification of fetal liver stroma in spectral cytometry using the parameter autofluorescence. Issue 11 (14th May 2022) - Peixoto, Márcia Mesquita; Soares‐da‐Silva, Francisca; Schmutz, Sandrine; Mailhe, Marie‐Pierre; Novault, Sophie; Cumano, Ana; Ait‐Mansour, Cedric
Abstract: The fetal liver (FL) is the main hematopoietic organ during embryonic development. The FL is also the unique anatomical site where hematopoietic stem cells expand before colonizing the bone marrow, where they ensure life‐long blood cell production and become mostly resting. The identification of the different cell types that comprise the hematopoietic stroma in the FL is essential to understand the signals required for the expansion and differentiation of the hematopoietic stem cells. We used a panel of monoclonal antibodies to identify FL stromal cells in a 5‐laser equipped spectral flow cytometry (FCM) analyzer. The "Autofluorescence Finder" of SONY ID7000 software identified two distinct autofluorescence emission spectra. Using autofluorescence as a fluorescence parameter we could assign the two autofluorescent signals to three distinct cell types and identified surface markers that characterize these populations. We found that one autofluorescent population corresponds to hepatoblast‐like cells and cholangiocytes whereas the other expresses mesenchymal transcripts and was identified as stellate cells. Importantly, after birth, autofluorescence becomes the unique identifying property of hepatoblast‐like cells because mature cholangiocytes are no longer autofluorescent. These results show that autofluorescence used as a parameter in spectral FCM is a useful tool to identify new cell subsets that are difficult to analyze in conventional FCM.